Management of Competent’s School Brand Image in Sman 1 Panumbangan, Ciamis District West Java - Artadinan, Dan; Komara, Endang; Sudrajat, Yogi; Adhiprasiano, Hudda (Fakultas Ekonomi Universitas Garut, 2024)
The increasingly rapid development of the times has led to the emergence of dynamics in people's thinking which has become more critical in choosing educational institutions. A school that develops with the competence of each of its human resources can create a positive image, that the school is a competent school. The research was conducted with the aim of: 1) formulating the competencies that need to be achieved by school principals, teachers, education staff and students at SMAN 1 Panumbangan to build a competent school, and 2) knowing the brand image management activities of competent schools at SMAN 1 Panumbangan. The type of research used is descriptive qualitative and data collection is carried out through interviews, observation and documentation. The research results show that competency standards are absolute things to have as basic competencies for employees, including students. Additional competencies for school principals include ICT competencies, financial analysts and supervisors. Additional competencies for teachers adapt to their areas of expertise as well as ICT and project manager competencies which really support learning in the independent curriculum. The competencies of educational staff adjust to their job position, while additional competencies for students adjust to the skills required in the world of work for high school qualifications. Brand image management is carried out by directing the achievement of competency standards and additional competencies achieved by school principals, teachers, education staff and students which are then published so that they are known to the wider community as school achievements.